2020
DOI: 10.1017/s1047951120002000
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cardiac interventions during the peak phase of COVID-19 pandemics in the country in a pandemics hospital in Istanbul

Abstract: Abstract Introduction: In this report, we aim to present our algorithm and results of patients with congenital cardiac disorders who underwent surgical or interventional procedures during the peak phase of the pandemics in our country. Patients and methods: The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…27 Despite all the facts regarding increased mortality and morbidity as well as deteriorated laboratory features, Ugurlucan et al indicated safe cardiac procedures in pediatric population with meticulous care and precautions. 28…”
Section: Discussionmentioning
confidence: 99%
“…27 Despite all the facts regarding increased mortality and morbidity as well as deteriorated laboratory features, Ugurlucan et al indicated safe cardiac procedures in pediatric population with meticulous care and precautions. 28…”
Section: Discussionmentioning
confidence: 99%